Comprehensive Review of COIN Strategies for Patients with Cancer - Nasser Aqeel Nasser Alhajji et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Cancer care has evolved significantly with the introduction of COIN (Cancer Optimization and Integration Network) strategies that aim to improve outcomes for patients. These strategies focus on integrating multidisciplinary care, patient-centered approaches, and innovative technologies. COIN strategies prioritize personalized treatment plans, coordinated care, and the inclusion of mental health support to enhance quality of life and survival rates. This review examines the core components of COIN strategies in oncology, their benefits, challenges, and their potential impact on the holistic care of cancer patients. Received Date: November 06, 2024 Accepted Date: November 27, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/253 https://doi.org/10.5281/zenodo.14251285